Database on spermatozoa transcriptogram of catagorised Frieswal crossbred (Holstein Friesian X Sahiwal) bulls - Singh, Rani; Junghare, Vivek; Hazra, Saugata; Singh, Umesh; Sengar, Gyanendra Singh; Raja, T.V.; Kumar, Sushil; Tyagi, Shrikant; Das, A.K.; Kumar, Ashish; Koringa, Prakash; Jakhesara, Subhash; et al. (Theriogenology, 2019)
Bull spermatozoa contain different functional genes and many of them plays important roles in different stages of spermatogenesis, spermatozoa kinetics, fertilization as well as embryonic development. RNA deep sequencing is one of the preferred tools for absolute quantification of messenger RNA. The intention of the current study was to investigate the abundance of spermatozoal transcripts in categorized Frieswal (Holstein-Friesian X Sahiwal) crossbred bull semen through RNA deep sequencing. A total 1546561 and 1019308 numbers of reads were identified among good and poor quality bull spermatozoa based on their conception rate. Post mapping with Bos taurus reference genome identified 1,321,236 and 842,022 number of transcripts among good and poor quality RNA libraries, respectively. However, a total number of 3510 and 6759 functional transcripts were identified among good and poor quality bull spermatozoa, respectively. Most of the identified transcripts were related to spermatozoa functions, embryonic development and other functional aspects of fertilization. Wet laboratory validation of the top five selected transcripts (AKAP4, PRM1, ATP2B4, TRIM71 and SLC9B2) illustrated the significant (p < 0.01) level of expression in the good quality crossbred bull semen than the poor quality counterparts. The present study with comprehensive profiling of spermatozoal transcripts provides a useful non-invasive tool to understand the causes of as well as an effective way to predict male infertility in crossbred bulls. •A total number of 3510 and 6759 functional genes were identified among good and poor quality bull spermatozoa, respectively.•AKAP4, PRM1, ATP2B4, TRIM71 and SLC9B2 were significantly expressed in good quality bull semen in comparison to poor one.•Comprehensive profiling of spermatozoal transcripts, provides an insight to predict the male infertility in crossbred bulls.